2019
DOI: 10.1177/1474515119885325
|View full text |Cite
|
Sign up to set email alerts
|

Tele-rehabilitation and hospital-based cardiac rehabilitation are comparable in increasing patient activation and health literacy: A pilot study

Abstract: Background: Cardiac tele-rehabilitation is defined as using information and communication technology to support rehabilitation services. However, it requires a high level of patient activation and health literacy; this has not yet been explored. Aims: The purpose of this study was to evaluate patient activation and health literacy in tele-rehabilitation compared to hospital-based cardiac rehabilitation. Methods: We conducted a pilot study in patients with ischaemic or heart valve disease. In a non-randomised d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 36 publications
2
45
0
6
Order By: Relevance
“…Eighteen studies were randomised and included 1 cross over design [50], 5 cluster randomised [39,41,44,47,51] and 12 individually randomised trials [30-32, 34, 36-38, 40, 43, 45, 49, 52]. The remaining four were quasi-experimental pre-post controlled trials [33,35,42,48]. Studies took place in nine countries -USA [30,31,37,39,40,42,43,45], Australia [35,51,52], Iran [32,34,47], China [41,44], Japan [36,49], Taiwan [48], Niger [38], Germany [50] and Demark [33].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen studies were randomised and included 1 cross over design [50], 5 cluster randomised [39,41,44,47,51] and 12 individually randomised trials [30-32, 34, 36-38, 40, 43, 45, 49, 52]. The remaining four were quasi-experimental pre-post controlled trials [33,35,42,48]. Studies took place in nine countries -USA [30,31,37,39,40,42,43,45], Australia [35,51,52], Iran [32,34,47], China [41,44], Japan [36,49], Taiwan [48], Niger [38], Germany [50] and Demark [33].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies focused on the domain of disease prevention (cancer screening [39] and malaria health literacy [38]), eight focused on healthcare (diabetes [30,37], gestational diabetes [32], breast cancer [36], cardiac conditions [33,34], one or more chronic conditions [35] and people taking two or more medications daily [31]). The remaining 12 studies focused on health promotion with eight focusing on general health promotion [41,42,44,45,48,[50][51][52], two focusing on nutrition [40,43], one on nutrition and physical activity [49] and one on smoking prevention [47].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mattson et al found that health literacy was associated with increased knowledge gain from cardiac patient education during a rehabilitation program [23]. A few intervention studies have also successfully addressed health literacy in their intervention design or measured it as an outcome [24,25]. In all these studies, as in most studies on health literacy in people with cardiac conditions, individual health literacy was measured using a single value or category [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%